Re-evaluation of the psychometric properties of the Serbian version of the Primary Sjögren’s Syndrome Quality of Life questionnaire - Vujović Sanja; Desnica Jana; Stevanović Momir; Veselinović Mirjana; Lučić-Tomić Aleksandra; Milovanović Dragan (Vojnosanitetski Pregled)
nema